Concurrence of imatinib-induced massive pleural/pericardial effusion and Campylobacter bacteremia in an adolescent with chronic myeloid leukemia. Issue 1 (January 2022) - Su, Po-Yu; Tan, Boon Fatt; Fu, Chun-Min; Chen, Chi-Nien; Chou, An-Kuo; Kung, Po-Jung; Liao, Ling-Chun; Li, Meng-Ju
Abstract: Imatinib is a crucial therapeutic strategy against chronic myeloid leukemia. Though superficial edema is a common adverse effect of imatinib, massive fluid retention is rarely reported. Here, we report the case of an adolescent who had tolerated imatinib for a long time, and then presented with massive pleural/pericardial effusion during an episode of Campylobacter jejuni bacteremia. A stepwise and comprehensive survey excluded all other plausible causes of disease. The Naranjo scale was used to assess the probability of an adverse effect of medication, and the score turned out to be 9, indicating severe fluid retention to be a definite reaction to imatinib. Drug discontinuation, antibiotic administration, and invasive procedures improved this condition. After this episode, the patient could tolerate imatinib again, illustrating the transient and reversible nature of this reaction. Since prolonged imatinib usage is crucial for chronic myeloid leukemia control, alertness to drug-related adverse effects is recommended, even if the subject has previously shown a good tolerance to the drug due to various physical conditions, especially physiological stressors, like infection or inflammation.